PENGARUH MOTIVASI DAN KEDISIPLINAN TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V DI SDN GLAGAHARUM - Nurul Aini; Imroatul Mufidah (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
Improving the learning achievement of students is an effort to improve the quality of education. The factors that affect the low learningachievementof student include internal and external factors. This research aims to describe how motivation and discipline affect the learning achievementof fifth grade students at SDN Glagaharum. The independent variable in this study are motivation an discipline, then the dependent variables are the result of learning. The instrument used to collect and obtain respondents data on motivation and discipline in this study is a questionnaire, data analysts use regressin analysis. Based on the results of the research that has been done, it is concluded that there is a significant influence between motivation and discipline of learning on the learnig outcomes of students in fifth grade at SDN Glagaharum. Given how important motivation and discipline are to learning outcomes, there needs to be high motivation and discipline in students to achieve the desired achievement